Towards the world’s first nuclear clock - Hellinger, Aaron C. (Kansas State University, 2022)
Since the concept of time was invented, scientists have striven to measure it as accurately as possible. Time-keeping devices have evolved throughout the years from ancient clepsydrae water clocks to the most sophisticated atomic clocks. It has now been theorized that a nuclear clock based on an isomeric transition of ²²⁹Th will become the new time standard with a precision error that decreases from 10^-15 to 10^-20 without any improvement upon the accuracy of the measurement of a second [1]. Before a prototype nuclear clock can be created, an exact energy measurement of the lowest known isomeric transition in ²²⁹Th, approximately 8 eV, must be performed. Current laser technology has become advanced enough that the idea of creating a laser with a wavelength near the transition energy, approximately 150 nm, is no longer an unrealistic idea. This thesis covers the efforts taken to construct an apparatus that collects ²²⁹Th³⁺ ions. A custom-made ²²⁹Th beam line has been designed and constructed that gathers decays from ²³³U and initially filters out all negatively charged ions and electrons inside a gas stopping cell that is backfilled with ultra high purity helium gas that is used to control charge exchange as well as cool the ions as they progress forward. These ions are focused into a beam using a 2D radiofrequency (RF) funnel and gathered by an RF quadrupole (RFQ). The newly gathered beam is guided into a mass separation quadrupole that filters out all undesired ions. The new ²²⁹Th³⁺ ion beam is then guided into a linear Paul ion trap for laser interrogation. While this thesis work does not complete the goal of trapping approximately 1,000,000 ²²⁹Th³⁺ ions (explained in Chapter 6), a fraction of the goal has been achieved. As of the time this thesis was written, the optimized ion trap has been able to contain 374,000 ²²⁹Th³⁺ ions, which is a factor of 200 times greater than the next largest linear Paul ion trap used for the detection of [superscript 229m]Th. Many improvements to the original apparatus have been performed and additional improvements are in the design process.
Keywords: Nuclear clock; Ion trap; Quadrupole; Thorium; Mass separation; Radiofrequency